Strategi Pemasaran Keripik Nenas di Desa Kualu Nenas Kecamatan Tambang Kabupaten Kampar - Puspita Sari Dewi; Evy Maharani; Susy Edwina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purpose of this research is to knowing the marketing channel of pineapple chips, to analyze marketing efficiency of pineapple chips, to analyze marketing mix of pineapple chips and to identify aspects of strengths, weaknesses, opportunities and threats and formulate strategies that can be applied in development agroindustry pineapple chips. The analityc method used in this research is survey method with sample 12 craftsmen. The reseach result shows there are two marketing channels pineapple chips are directly and indirectly. Marketing efficiency at direct and indirect marketing channel there is the same in the plastic 250gr packaging. Product strategies with respect to product attributes, branding, gift packaging, labeling and product support services. Pricing strategies based on cost and competition. Distribution strategies are directly to consumers, through retailers and wholesalers. Promotion strategies are personal selling, sales promotion and direct marketing. Pineapple chips marketing strategy are participation in training in order to development business, increase production, cooperation with the government to finding alternative problems solutions and utilizing media promotion. Keywords : Agroindustry, marketing mix, marketing strategy